Mamminasata BRT User Trip Characteristics for the Design of Demand Modelling Method for a New BRT Line - Suprayitno, Hitapriya; Ananda Upa, Verdy (IPTEK The Journal for Technology and Science, 2016)
Indonesia started to developed largely the MRT line, especially the BRT. A new BRT Corridor implementation need a Passenger Demand Prediction. Thus, a Special BRT Passenger Demand Modelling Method for a New BRT Line need to be developed. This attempt needs a sufficient knowledges on the Existing BRT User Trip Characteristics. Mamminasata BRT User Trip Characteristics Survey were executed on Corridor 2 and Corridor 3, during morning peak hour. The result indicates that the BRTs are used mainly for schooling and working trips, the BRT passengers are the previous public transport and motorcycle users. The trip origin zone is extended 3 km to the left and to the right of the BRT corridor, while the trip destination zone is extended 1.5 km to the left and to the right of the BRT corridor. The embarking connecting trip modes are dominated by motorcycle, public transport and becak, while the alighting connecting trip modes are dominated by walking tri